Intravascular papillary endothelial hyperplasia (Masson's tumor) in hallux nail matrix: a case report - Marielle de Godoi Spader; Ana Paula Naspolini; Sérgio Emerson Sasso; Tassiana de Boit Milanez; Guilherme Suchard (Sociedade Brasileira de Dermatologia (SBD), 2022)
Intravascular endothelial hyperplasia, or Masson's tumor, is a benign vascular lesion with no well-defined pathogenesis.The response to vascular damage is believed to be one of the main reasons for its development. It is a typically painless injury, solitary, with slow evolution. This report aims to describe a case of Masson's tumor in an unusual place, the hallux nail matrix, and discuss its main characteristics.